The inside/outside dichotomy in Plato’s «Phaedrus» - Lavilla de Lera, Jonathan (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
In Plato’s Phaedrus, not only the inside/outside dichotomy is explicitly used by Socrates three times, but it is implicitly suggested in many other passages. The current paper analyses in their context the different texts in which the dichotomy is employed, trying to show that, by means of it, Plato aims to distinctly define the philosophic way of life, clearly distinguishing it from the rest of modi vivendi.
Keywords: Plato; Phaedrus; dialectic; rhetoric